Pemanfaatan Tanah Belum Lunas - Nursaidah Nursaidah; Zulfan Efendi Hasibuan (Jurnal El-Thawalib, 2021)
The problem of this research is basically a review of Islamic law on the use of the object of buying and selling land that has not been paid off in Simangambat Village, Siabu District, Mandailing Natal Regency. The formulation of the problem of this research is the use of the object of sale and purchase that has not been paid off by the buyer of the land and the view according to Islamic law. The purpose of this study was to find out how Islamic law reviews the utilization of the object of buying and selling land that has not been paid off in Simangambat Village, Siabu District, Mandailing Natal Regency.The basic theory used in this study is the understanding of buying and selling, the legal basis of buying and selling, the pillars and terms of buying and selling, various kinds of buying and selling, the wisdom and benefits of buying and selling, elements of negligence in buying and selling, forms of buying and selling, obligations of sellers and buyers , understanding of buying and selling credit, the legal basis of buying and selling credit, terms and conditions of buying and selling credit, and the consequences of buying and selling credit.This research is a field research, research used to collect data on phenomena that occur, natural and scientific. The data sources of this research are primary data and secondary data. Research data collection techniques using field studies (observations, interviews and documentation) and library studies. And use a systematic discussion.The results of the research that are expressed in the thesis entitled Islamic law review on the use of the object of buying and selling land that have not been paid off in Simangambat village, Siabu district, Mandailing Natal district are the terms and pillars of buying and selling are in accordance with Islamic law but the problem here is that the buyer does not occupy the agreement that has been made at the beginning of the transaction and here the seller feels aggrieved and causes a broken promise.